Lithiation/delithiation synthesis of few layer silicene nanosheets for rechargeable Li-O2 batteries - Zhang, Wenyu (2019)
Silicene has recently received increasing interest due to its unique properties. However, the synthesis of silicene remains challenging, which limits its wide applications. In this work, a top‐down lithiation and delithiation process is developed to prepare few layer silicene‐like nanosheets from ball‐milled silicon nanopowders. It is found that delithiation solvent plays a critical role in the structure evolution of the final products. The use of isopropyl alcohol renders 2D silicene‐like products 30–100 nm in length and ≈2.4 nm in thickness. The electrochemical characterization analysis suggests that the product shows high performance for rechargeable Li–O2 batteries with 73% energy efficiency and high stability. The top‐down synthesis strategy proposed in this work not only provides a new solution to the challenging preparation issue of few layer silicene but also demonstrates the feasibility of producing 2D materials from nonlayered starting structures.